Rekonsruksi Tahapan Pembentukan Perundang-undangan: Urgensi Re-Harmonisasi dan Evaluasi sebagai Siklus Pembentukan Undang-undangan yang Berkualitas - Chandra, M Jeffri Arlinandes; anggono, bayu dwi; Febrian, Febrian (Jurnal Legislasi Indonesia, 2022)
Indonesia is a state based on laws and regulations which are formed as basic rules in the state and society. The law as the main basis must be formed in accordance with the principles of establishing good laws and regulations so that it is hoped that later it can be applied and has binding legal force for all levels of society. The current situation is far from expectations for the formation of a good law, for example the formation of a job creation law which is considered not to actively involve the community, many articles are contrary to legal principles, are harmonized and synchronized between statutory regulations, the formation of laws that seem rushed so there are many errors in writing (typo) and much more. Therefore, it is necessary to reconstruct stages in order to at least achieve the desired expectations in the formation of a good law. This paper uses normative research with a statutory approach, a comparative approach, and finally concludes with a conceptual approach where concepts that are considered suitable can be applied in Indonesia. 2 things that become important highlights in this paper are First, the practice of harmonization, synchronization and consolidation of conceptions that have been well implemented but only exist at the planning and drafting stages of the Draft Law, while after the discussion/Mutual agreement (plenary) there are great opportunities regarding changes the changes that occurred which made it very possible for the disharmony and synchronization of the bill to be ratified, then secondly, the issue of public participation which seemed to be a complementary ingredient in the formation of the law, therefore this paper provides the best solution for reviewing (preview) a bill before it is passed so that there is a review. harmonization and also means of education, consultation and publication of pre-ratification and promulgation of laws to be ratified